PCO composite filter element material, composite filter element and water purification equipment
By modifying natural rock materials and reasonably proportioning, PCO composite filter material is used to adjust the pH value of the water body, the problem of the existing water purifier being weakly acidic, and the water effluent is realized as weakly alkaline water suitable for human drinking, ensuring human health.
Patent Information
- Application Number
- CN202411722149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water purifiers are all weakly acidic, with a pH between 5.5-6.5, which is not suitable for long-term drinking and cannot provide weakly alkaline water suitable for human health.
The PCO composite filter element material is used to modify the natural rock materials and the reasonable proportion of various rock materials to stabilize the pH of the filter element, so that the effluent water quality remains weak alkaline suitable for human drinking.
The pH value of the water is adjusted through the filter element material, so that the water is weakly alkaline suitable for human drinking, and has a positive effect on protecting human health.
Smart Images

Figure BDA0005158311710000061 
Figure BDA0005158311710000071 
Figure BDA0005158311710000081
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of water purification equipment, and more specifically, relates to a PCO composite filter element material, a composite filter element and a water purification equipment. Background Art
[0002] As people's living standards improve, their requirements for drinking water quality are gradually increasing, and water purifiers are becoming more and more common in households. The normal pH of human tissue is between 7.0-7.4, and the normal pH of blood is between 7.35-7.45. Drinking weak alkaline water is essential for protecting human health. However, the water produced by existing water purifiers is weakly acidic, with a pH between 5.5-6.5, which is not conducive to long-term drinking. For this reason, we propose a PCO composite filter element material, a composite filter element, and a water purification device. Summary of the invention
[0003] To achieve the above objectives, the technical solution adopted in this application is: in the first aspect, a PCO composite filter element material is provided, comprising the following raw materials in parts by weight: 65 to 75 parts of modified medical stone, 60 to 80 parts of modified serpentine, 75 to 85 parts of modified calcite, and 30 to 50 parts of activated carbon.
[0004] Optionally, the particle sizes of the modified medical stone, the modified serpentine, the modified calcite and the activated carbon are all 1 to 3 mm.
[0005] Optionally, the modified medical stone is prepared by the following method:
[0006] A1. Crushing natural medical stone into particles with a diameter of 3 to 6 mm;
[0007] A2, the medical stone particles are activated in a muffle furnace, the activation temperature is 250 ℃ ~ 300 ℃, the activation time is 3 ~ 5 hours;
[0008] A3, soak the activated medical stone particles in 0.5-1.5 mol / L NaCl solution, control the temperature to 75°C-85°C, and then wash them in an ultrasonic environment for 3 hours;
[0009] A4, ultrasonically wash the medical stone particles with deionized water for 30 min, then dry them in a ventilated environment at 150°C, and finally cool them to room temperature;
[0010] A5. Crush the cooled medical stone particles, and pass them through 3 mm and 1 mm sieves in turn to obtain modified medical stone with a particle size of 1 to 3 mm.
[0011] Optionally, the activation temperature is controlled to be increased to 250° C. to 300° C. at a rate of 10° C. / min.
[0012] Optionally, the modified serpentine is prepared by the following method:
[0013] B1. Crush the natural serpentine into particles with a diameter of 1 to 2 cm and rinse them clean;
[0014] B2. Soak the cleaned serpentine particles in dilute hydrochloric acid for 3 hours, and then rinse them with deionized water;
[0015] B3, adjust the pH value of the serpentine particles to 7.0 with an alkaline solution, and then rinse with deionized water;
[0016] B4, drying the serpentine particles, and then heating them in a muffle furnace to a constant temperature of 390°C to 410°C for 2 hours;
[0017] B5. The serpentine particles are cooled and crushed, and passed through 3 mm and 1 mm sieves in turn to obtain modified serpentine with a particle size of 1 to 3 mm.
[0018] Optionally, the alkaline solution is a Ca(OH)2 solution with a concentration of 0.001 to 0.002 mol / L.
[0019] Optionally, the modified calcite is prepared by the following method:
[0020] C1. Crushing natural macrocrystalline calcite into particles with a diameter of 5 to 8 mm and washing them clean;
[0021] C2. Soak the calcite particles in 0.5 mol / L acetic acid solution for 3 hours and then wash them with deionized water;
[0022] C3, drying the calcite particles in a ventilated environment at 90°C to 100°C, and then keeping the dried calcite particles at a constant temperature of 240°C to 260°C in an atmosphere of carbon dioxide and water vapor for 2 hours;
[0023] C4. After cooling in air isolation, the calcite is crushed and passed through 3 mm and 1 mm sieves in turn to obtain modified calcite with a particle size of 1 to 3 mm.
[0024] Optionally, the activated carbon is coconut shell activated carbon.
[0025] In a second aspect, the present application further provides a composite filter element, comprising a shell, wherein the PCO composite filter element material provided in the first aspect is arranged in the shell.
[0026] In a third aspect, the present application further provides a water purification device, which includes the PCO composite filter element material provided in the first aspect or the composite filter element provided in the second aspect.
[0027] The beneficial effect of the PCO composite filter element material provided by the present application is that, compared with the prior art, the present application stably adjusts the pH value of the water passing through the filter element by modifying the natural rock material and reasonably matching various rock materials, so that the effluent water quality remains weakly alkaline water suitable for human drinking, which has a positive effect on protecting human health. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] The PCO composite filter element material, composite filter element and water purification equipment provided in the embodiments of the present application are now described.
[0030] In a first aspect, the present application provides a PCO composite filter element material, comprising the following raw materials in parts by weight: 65 to 75 parts of modified medical stone, 60 to 80 parts of modified serpentine, 75 to 85 parts of modified calcite, and 30 to 50 parts of activated carbon.
[0031] Preferably, the PCO composite filter element material comprises the following raw materials in parts by weight: 70 parts of modified medical stone, 70 parts of modified serpentine, 80 parts of modified calcite, and 40 parts of activated carbon.
[0032] In some embodiments of the present application, the particle sizes of the modified medical stone, the modified serpentine, the modified calcite and the activated carbon are all 1 to 3 mm.
[0033] In some embodiments of the present application, the modified medical stone is prepared by the following method:
[0034] A1. Crushing natural medical stone into particles with a diameter of 3 to 6 mm;
[0035] A2, the medical stone particles are activated in a muffle furnace, the activation temperature is 250 ℃ ~ 300 ℃, the activation time is 3 ~ 5 hours;
[0036] A3, soak the activated medical stone particles in 0.5-1.5 mol / L NaCl solution, control the temperature to 75°C-85°C, and then wash them in an ultrasonic environment for 3 hours;
[0037] A4, ultrasonically wash the medical stone particles with deionized water for 30 min, then dry them in a ventilated environment at 150°C, and finally cool them to room temperature;
[0038] A5. Crush the cooled medical stone particles, and pass them through 3 mm and 1 mm sieves in turn to obtain modified medical stone with a particle size of 1 to 3 mm.
[0039] In some embodiments of the present application, the activation temperature is controlled to be increased to 250° C. to 300° C. at a rate of 10° C. / min.
[0040] In some embodiments of the present application, the modified serpentine is prepared by the following method:
[0041] B1. Crush the natural serpentine into particles with a diameter of 1 to 2 cm and rinse them clean;
[0042] B2. Soak the cleaned serpentine particles in dilute hydrochloric acid for 3 hours, and then rinse them with deionized water;
[0043] B3, adjust the pH value of the serpentine particles to 7.0 with an alkaline solution, and then rinse with deionized water;
[0044] B4, drying the serpentine particles, and then heating them in a muffle furnace to a constant temperature of 390°C to 410°C for 2 hours;
[0045] B5. The serpentine particles are cooled and crushed, and passed through 3 mm and 1 mm sieves in turn to obtain modified serpentine with a particle size of 1 to 3 mm.
[0046] In some embodiments of the present application, the alkaline solution is a Ca(OH)2 solution with a concentration of 0.001-0.002 mol / L. Calcium hydroxide is slightly soluble and the amount of dissolution is not large; secondly, calcium hydroxide is an alkaline solution, which can effectively neutralize the acid remaining in the previous step; in addition, some calcium ions can remain in the modified serpentine, providing a richer variety of minerals.
[0047] In some embodiments of the present application, the modified calcite is prepared by the following method:
[0048] C1. Crushing natural macrocrystalline calcite into particles with a diameter of 5 to 8 mm and washing them clean;
[0049] C2. Soak the calcite particles in 0.5 mol / L acetic acid solution for 3 hours and then wash them with deionized water;
[0050] C3, drying the calcite particles in a ventilated environment at 90°C to 100°C, and then keeping the dried calcite particles at a constant temperature of 240°C to 260°C in an atmosphere of carbon dioxide and water vapor for 2 hours;
[0051] C4. After cooling in air isolation, the calcite is crushed and passed through 3 mm and 1 mm sieves in turn to obtain modified calcite with a particle size of 1 to 3 mm.
[0052] In some embodiments of the present application, the activated carbon is coconut shell activated carbon.
[0053] In a second aspect, the present application further provides a composite filter element, comprising a shell, wherein the PCO composite filter element material provided in the first aspect is arranged in the shell.
[0054] In a third aspect, the present application further provides a water purification device, which includes the PCO composite filter element material provided in the first aspect or the composite filter element provided in the second aspect.
[0055] This application modifies natural rock materials and, through reasonable proportions of various rock materials, stably adjusts the pH value of water passing through the filter element, so that the effluent water quality remains weakly alkaline water suitable for human drinking, which plays a positive role in protecting human health.
[0056] Example 1
[0057] Evenly mix 70g of modified medical stone, 70g of modified serpentine, 80g of modified calcite and 40g of coconut shell activated carbon. Put the mixed materials into a small T filter shell to make a small T size filter element.
[0058] In Example 1, 1 g is 1 portion.
[0059] The modified medical stone in this embodiment is obtained by the following method:
[0060] A1. Crushing natural medical stone into particles with a diameter of 3 to 6 mm;
[0061] A2, activate the medical stone particles in a muffle furnace, the activation target temperature is 260 ° C, and the activation time is 4 hours;
[0062] A3, the activated medical stone particles were immersed in 1.0 mol / L NaCl solution, the temperature was controlled at 75°C to 77°C, and then washed in an ultrasonic environment for 3 hours;
[0063] A4, ultrasonically wash the medical stone particles with deionized water for 30 min, then dry them in a ventilated environment at 150°C, and finally cool them to room temperature;
[0064] A5. Crush the cooled medical stone particles, and pass them through 3 mm and 1 mm sieves in turn to obtain modified medical stone with a particle size of 1 to 3 mm.
[0065] The modified serpentine in this embodiment is obtained by the following method:
[0066] B1. Crush the natural serpentine into particles with a diameter of 1 to 2 cm and rinse them clean;
[0067] B2. Soak the cleaned serpentine particles in 0.5 mol / L dilute hydrochloric acid for 3 hours, and then rinse with deionized water;
[0068] B3. Adjust the pH value of the serpentine particles to 7.0 with Ca(OH)2 solution, and then rinse with deionized water;
[0069] B4, drying the serpentine particles, and then heating them in a muffle furnace to a constant temperature of 390°C to 395°C for 2 hours;
[0070] B5. The serpentine particles are cooled and crushed, and passed through 3 mm and 1 mm sieves in turn to obtain modified serpentine with a particle size of 1 to 3 mm.
[0071] The modified calcite in this embodiment is obtained by the following method:
[0072] C1. Crushing natural macrocrystalline calcite into particles with a diameter of 5 to 8 mm and washing them clean;
[0073] C2. Soak the calcite particles in 0.5 mol / L acetic acid solution for 3 hours and then wash them with deionized water;
[0074] C3, drying the calcite particles in a ventilated environment at 90°C to 100°C, and then keeping the dried calcite particles at a constant temperature of 240°C to 245°C in an atmosphere of carbon dioxide and water vapor for 2 hours;
[0075] C4. After cooling in air isolation, the calcite is crushed and passed through 3 mm and 1 mm sieves in turn to obtain modified calcite with a particle size of 1 to 3 mm.
[0076] According to the requirements of the "Sanitary Safety Evaluation Standard for Drinking Water Distribution Equipment and Protective Materials", a sanitary safety immersion test was carried out. The immersion results are shown in Table 1, where PCO1 and PCO2 are parallel experiments conducted using the filter element prepared in Example 1.
[0077] Table 1 Example 1 Preparation filter element immersion data
[0078]
[0079]
[0080]
[0081] The blank in this embodiment refers to the filter housing that is used directly without filling the filter material.
[0082] Install the filter element at the end of the pure water machine and continuously pass water at a flow rate of 1.5L / min. Rinse for 30 minutes and start calculating the water flow rate, which is recorded as 0L. When the water flow rate reaches 0L, 1250L, 2500L, 3750L, and 5000L, samples are taken to test TDS and pH. The test results are shown in Table 2:
[0083] Table 2 Water flow data of filter element prepared in Example 1
[0084]
[0085] It can be seen from the experimental data that the PCO filter element material provided in this application is hygienic and safe in compliance with relevant national regulations, and its release is relatively stable under water conditions.
[0086] Comparative Example 1-1
[0087] Mix 50g of modified medical stone, 70g of modified serpentine, 80g of modified calcite and 40g of coconut shell activated carbon evenly. Put the mixed materials into a small T filter shell to make a small T size filter element.
[0088] The modified medical stone, modified serpentine, modified calcite and coconut shell activated carbon used in this comparative example are consistent with the materials used in Example 1.
[0089] In Comparative Example 1-1, 1 g is 1 portion.
[0090] According to the requirements of the "Sanitary Safety Evaluation Standard for Drinking Water Transmission and Distribution Equipment and Protective Materials", a sanitary safety immersion test was carried out. The immersion results are shown in Table 3.
[0091] Table 3 Immersion data of filter element prepared in comparative example 1-1
[0092]
[0093]
[0094] The blank in this comparative example refers to the filter housing which is used directly without filling the filter material.
[0095] By comparing the sanitary safety immersion data of Example 1 and Comparative Example 1-1, it can be found that reducing the amount of modified medical stone added will have a greater impact on the change in pH value, resulting in unqualified items.
[0096] Comparative Example 1-2
[0097] 90g of modified medical stone, 70g of modified serpentine, 80g of modified calcite and 40g of coconut shell activated carbon were mixed evenly. The mixed materials were loaded into a small T filter shell to make a small T size filter element.
[0098] The modified medical stone, modified serpentine, modified calcite and coconut shell activated carbon used in this comparative example are consistent with the materials used in Example 1.
[0099] In Comparative Example 1-2, 1 g is 1 portion.
[0100] According to the requirements of the "Sanitary Safety Evaluation Standard for Drinking Water Transmission and Distribution Equipment and Protective Materials", a sanitary safety immersion test was carried out. The immersion results are shown in Table 4.
[0101] Table 4 Immersion data of filter element prepared in Comparative Example 1-2
[0102]
[0103]
[0104] The blank in this comparative example refers to the filter housing which is used directly without filling the filter material.
[0105] By comparing the sanitary safety immersion data of Example 1 with those of Comparative Examples 1-2, it can be found that increasing the amount of modified medical stone added will increase the amount of heavy metal aluminum precipitated, thus resulting in failure to meet the standards.
[0106] Comparative Example 2
[0107] Mix 70g of modified medical stone, 70g of serpentine stone, 80g of modified calcite and 40g of coconut shell activated carbon evenly. Put the mixed materials into a small T filter shell to make a small T size filter element.
[0108] In this comparison 1, 1 g is 1 serving.
[0109] Install the prepared filter element at the end of the pure water machine and continuously pass water at a flow rate of 1.5L / min. Rinse for 30 minutes and start calculating the water flow rate, which is recorded as 0L. When the water flow rate reaches 0L, 1250L, 2500L, 3750L, and 5000L, samples are taken to test TDS and pH. The test results are shown in Table 2:
[0110] Table 5 Comparative Example 2 Preparation Filter Water Passage Data
[0111]
[0112] By comparing the water flow data of Example 1 and Comparative Example 2, it can be found that when the filter element is configured with unmodified serpentine raw stone, the filter element performance decays significantly and fails to reach the expected value.
[0113] It should be noted that the modified medical stone, modified serpentine and modified calcite in this comparative example are prepared by the same method as in the embodiments, and therefore will not be described in detail in this comparative example.
[0114] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A PCO composite filter element material, characterized in that: The invention comprises the following raw materials in parts by weight: 65-75 parts of modified medical stone, 60-80 parts of modified serpentine, 75-85 parts of modified calcite and 30-50 parts of activated carbon.
2. The PCO composite filter element material according to claim 1, characterized in that: The particle sizes of the modified medical stone, the modified serpentine, the modified calcite and the activated carbon are all 1 to 3 mm.
3. The PCO composite filter element material according to claim 1, characterized in that: The modified medical stone is prepared by the following method: A1. Crushing natural medical stone into particles with a diameter of 3 to 6 mm; A2, the medical stone particles are activated in a muffle furnace, the activation temperature is 250 ℃ ~ 300 ℃, the activation time is 3 ~ 5 hours; A3, soak the activated medical stone particles in 0.5-1.5 mol / L NaCl solution, control the temperature to 75°C-85°C, and then wash them in an ultrasonic environment for 3 hours; A4, ultrasonically wash the medical stone particles with deionized water for 30 min, then dry them in a ventilated environment at 150°C, and finally cool them to room temperature; A5. Crush the cooled medical stone particles, and pass them through 3 mm and 1 mm sieves in turn to obtain modified medical stone with a particle size of 1 to 3 mm.
4. The PCO composite filter element material according to claim 3, characterized in that: The activation temperature was controlled to be raised to 250°C to 300°C at a rate of 10°C / min.
5. The PCO composite filter element material according to claim 1, characterized in that: The modified serpentine is prepared by the following method: B1. Crush the natural serpentine into particles with a diameter of 1 to 2 cm and rinse them clean; B2. Soak the cleaned serpentine particles in dilute hydrochloric acid for 3 hours, and then rinse them with deionized water; B3, adjust the pH value of the serpentine particles to 7.0 with an alkaline solution, and then rinse with deionized water; B4, drying the serpentine particles, and then heating them in a muffle furnace to a constant temperature of 390°C to 410°C for 2 hours; B5. The serpentine particles are cooled and crushed, and passed through 3 mm and 1 mm sieves in turn to obtain modified serpentine with a particle size of 1 to 3 mm.
6. The PCO composite filter element material according to claim 5, characterized in that: The alkaline solution is a Ca(OH)2 solution with a concentration of 0.001-0.002 mol / L.
7. The PCO composite filter element material according to claim 1, characterized in that: The modified calcite is prepared by the following method: C1. Crushing natural macrocrystalline calcite into particles with a diameter of 5 to 8 mm and washing them clean; C2. Soak the calcite particles in 0.5 mol / L acetic acid solution for 3 hours and then wash them with deionized water; C3, drying the calcite particles in a ventilated environment at 90°C to 100°C, and then keeping the dried calcite particles at a constant temperature of 240°C to 260°C in an atmosphere of carbon dioxide and water vapor for 2 hours; C4. After cooling in air isolation, the calcite is crushed and passed through 3 mm and 1 mm sieves in turn to obtain modified calcite with a particle size of 1 to 3 mm.
8. The PCO composite filter element material according to claim 1, characterized in that: The activated carbon is coconut shell activated carbon.
9. A composite filter element, characterized in that: It comprises a shell, in which the PCO composite filter element material according to any one of claims 1 to 8 is arranged.
10. A water purification device, characterized in that: It comprises the PCO composite filter element material according to any one of claims 1 to 8 or the composite filter element according to claim 9.
Citation Information
Patent Citations
Weakly alkaline composite filter element based on natural rock materials and preparation method thereof
CN110152399A